Inbreeding depression and heterosis in sweet corn varieties Manis Madu and Bakti-1 - Saleh, Ghizan; Yusop, Mohd Rafii; Yap, Thoo Chai (Universiti Putra Malaysia Press, 1993)
S1 and full-sib progeny families developed from selfing and crossing between Manis Madu and Bakti-1 sweet corn varieties were evaluated to estimate inbreeding depression and heterosis in the populations. Selfing has caused a significant decrease in the measurements of all characters taken in both selfed populations, except for days to tasseling which has shown an increase. Midparent heterosis estimates for the characters evaluated ranged from -2.83% to 22.34% for the Manis Madu X Bakti-1 cross progeny population (MMB1), and from -2.65% to 16.57% in the Bakti-1 X Manis Madu cross progeny population (B1MM). The two varieties revealed good potential to be used as parents for crosses between improved populations or inbred lines developed from them.